1999
DOI: 10.1002/(sici)1097-0223(199911)19:11<1067::aid-pd696>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive hydrocephalus due to congenital stenosis of the aqueduct of Sylvius

Abstract: Isolated hydrocephalus due to congenital stenosis of the aqueduct of Sylvius is almost always an X-linked recessive inherited condition. We describe a brother and sister with isolated hydrocephalus from congenital aqueductal stenosis. We believe that these two occurrences represent a rare autosomal recessive form of this abnormality. In assessing a first known occurrence of hydrocephalus with stenosis of the aqueduct of Sylvius in a family, the rare possibility of autosomal inheritance must be considered in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Animal models have established autosomal dominant and recessive patterns26 of inheritance for CH, and case studies in humans have added support to the existence of these patterns 18 – 25. Our results indicate that autosomal patterns of inheritance for CH are not rarities, but should be considered in familial cases of hydrocephalus in which X linked inheritance is unlikely.…”
Section: Discussionmentioning
confidence: 52%
“…Animal models have established autosomal dominant and recessive patterns26 of inheritance for CH, and case studies in humans have added support to the existence of these patterns 18 – 25. Our results indicate that autosomal patterns of inheritance for CH are not rarities, but should be considered in familial cases of hydrocephalus in which X linked inheritance is unlikely.…”
Section: Discussionmentioning
confidence: 52%
“…It seems likely that unrecognized genetic factors are responsible. In addition, a number of autosomal recessive forms have been reported (e.g., [1,7,16,44,51]). A genetic component for congenital hydrocephalus is indicated by the results of epidemiological studies [6,31,41,46].…”
Section: Discussionmentioning
confidence: 99%
“…It is etiologically diverse and not well understood. Although a number of familial forms have been reported [1,7,16,44,51], the molecular genetics have not been investigated. Although a number of familial forms have been reported [1,7,16,44,51], the molecular genetics have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A specific etiology has been identified in a few patients with primary AS. Haverkampf et al (13) found 37% x-linked recessive inheritance in patients with congenital primary AS and there are recent reports on both autosomal recessive (14,15) and autosomal dominant (16) forms of inheritance. Infections known to cause AS are toxoplasmosis [responsible for 15% of the cases reported by Hirsch et al (9)], mumps (17), aspergillos (18), Epstein-Barr virus (19), and CMV (20).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Haverkampf et al (13) found 37% x-linked recessive inheritance in patients with congenital primary AS and there are recent reports on both autosomal recessive (14,15) and autosomal dominant (16) forms of inheritance. Haverkampf et al (13) found 37% x-linked recessive inheritance in patients with congenital primary AS and there are recent reports on both autosomal recessive (14,15) and autosomal dominant (16) forms of inheritance.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%